Study Materials: ncert solutions

Our ncert solutions for Solutions 2. Polynomials - Exercise 2.4 | Class 9 Mathematics - Toppers Study is the best material for English Medium students cbse board and other state boards students.

 

Solutions ⇒ Class 9th ⇒ Mathematics ⇒ 2. Polynomials

Solutions 2. Polynomials - Exercise 2.4 | Class 9 Mathematics - Toppers Study

Topper Study classes prepares ncert solutions on practical base problems and comes out with the best result that helps the students and teachers as well as tutors and so many ecademic coaching classes that they need in practical life. Our ncert solutions for Solutions 2. Polynomials - Exercise 2.4 | Class 9 Mathematics - Toppers Study is the best material for English Medium students cbse board and other state boards students.

2. Polynomials

| Exercise 2.4 |

Solutions 2. Polynomials - Exercise 2.4 | Class 9 Mathematics - Toppers Study


Chapter 2. Polynomials


Exercise 2.4

Q.1. Determine which of the following polynomials has (x+ 1) a factor:

(i) x+x+ x +1                                        (ii) x+ x+ x+ x +1

(iii) x+ 3x+ 3x+ x +1                             

Solution:

(i) If (x + 1) is a factor of p(x) = x3+ x2+ x + 1, then p (−1) must be zero, otherwise (x + 1) is not a factor of p(x).

P(x)  = x+ x+ x + 1

P(−1)= (−1)+ (−1)+ (−1) + 1

         = − 1 + 1 − 1 − 1

        = 0

∵ P(x) = 0 

Hence, x + 1 is a factor of this polynomial.

(ii) If (x + 1) is a factor of p(x) = x4+ x3+ x2+ x + 1, then p (−1) must be zero, Otherwise (x + 1) is not a factor of p(x).

P(x) = x4+ x3+ x2+ x + 1

P(−1) = (−1)+ (−1)+ (−1)+ (−1) + 1

          = 1 − 1 + 1 −1 + 1

          = 1

As P(x) ≠ 0, (− 1)

Therefore, x + 1 is not a factor of this polynomial.

(iii) If (x + 1) is a factor of polynomial p(x) = x4+ 3x3+ 3x2+ x + 1, then p (−1) must  be 0, otherwise (x + 1) is not a factor of this polynomial.

P(x) = x4+ 3x3+ 3x2+ x + 1

P(−1) = (−1)4+ 3(−1)3+ 3(−1)2+ (−1) + 1

          = 1 − 3 + 3 − 1 + 1

          = 1

As P(x) ≠ 0, (−1) 

Therefore (x+1) is not a factor of this polynomial .

Q.2. Use the Factor Theorem to determine whether g(x) is a factor of p(x) in each of the following cases:

 (i)         P(x) = 2x3+ x2− 2x − 1, g(x) = x + 1

 (ii)        P(x) = x+ 3x+ 3x + 1, g(x) = x + 2

 (iii)       P(x) = x− 4 x+  x + 6, g(x) = x − 3 

Solution:

(i)   If g(x) = x + 1 is a factor of the given polynomial p(x), then p (−1) must be zero.

P (x) = 2x+ x− 2x − 1

P (−1) = 2(−1)3+ (−1)2− 2(−1) − 1

           = 2(−1) + 1 + 2 – 1   

           = 0

∵ P(x) = 0 

Hence, g(x) = x + 1 is a factor of the given polynomial.

(ii) If g(x) = x + 2 is a factor of the given polynomial p(x), then p (−2) must be 0.

P (x) = x3+3x2+ 3x + 1

P (−2) = (−2)3+ 3(−2)2+ 3(−2) + 1

           = − 8 + 12 − 6 + 1  

           = −1

As P(x) ≠ 0, 

Hence, g(x) = x + 2 is not a factor of the given polynomial.

(iii) If g(x) = x − 3 is a factor of the given polynomial p(x), then P(3) must be 0.

        P(x) = x3− 4 x2+ x + 6

        P(3) = (3)− 4(3)+ 3 + 6

                = 27 −36 + 9

                = 0

Hence, g(x) = x − 3 is a factor of the given polynomial. 

Solution:

: If x − 1 is a factor of polynomial p(x), then P(1) must be 0.

(i) P(x) = x2+ x + k

    P(1) = (1)2+ 1 + k

            = 1+1+ 

            = 2+k

        k  =−2 

(iv) P(x) = kx2-3x + k    

      P(1) = k(1)2-3(1) + k

             = k-3+k

        2k = 3

         K = 3/2

Question 4: Factorise: 

(i) 12x2− 7x + 1                           (ii) 2x2+ 7x + 3

(iii) 6x2+ 5x – 6                           (iv) 3x2− x − 4 

Solution:

(i) 12x2− 7x + 1 we can find two numbers,

Such that pq = 12 × 1 = 12 and p + q = −7.

They are p = −4 and q = −3

Here, 12x2− 7x + 1

      = 12x2− 4x − 3x + 1

      = 4x (3x − 1) − 1 (3x − 1)

      = (3x − 1) (4x − 1)

(ii) 2x2+ 7x + 3 we can find two numbers such that pq = 2 × 3= 6 and p + q = 7.

     They are p = 6 and q = 1.

     Here, 2x2 + 7x + 3

    = 2x2+ 6x + x + 3

    = 2x (x + 3) + 1 (x + 3)

    = (x + 3) (2x+ 1) 

(iii) 6x2+ 5x − 6 we can find two numbers such that pq = −36 and p + q = 5.

     They are p = 9 and q = −4.

     Here, 6x2+ 5x – 6

    = 6x2+ 9x − 4x – 6

    = 3x (2x + 3) − 2 (2x + 3)

    = (2x + 3) (3x − 2) 

(iv)  3x2− x − 4 we can find two numbers,

such that pq = 3 × (−4) = −12 and p + q = −1.

They are p = −4 and q = 3

Here, 3x2− x − 4

       = 3x2− 4x + 3x – 4

       = x (3x − 4) + 1 (3x − 4)

       = (3x − 4) (x + 1)

Question 5. Factorize:

 (i) x3− 2x2− x + 2                 (ii) x3+ 3x2−9x − 5

(iii) x3+ 13x2+ 32x + 20         (iv) 2y3+ y2− 2y – 1 

Solution:

 (i) Let P(x) = x3− 2x2− x + 2 all the factor are there. These are ± 1, ± 2.

By trial method, P (1) = (1)3− 2(1)2− 1 + 2

         = 1 − 2 − 1+ 2

         = 0 Therefore, (x − 1) is factor of polynomial p(x)

         Let us find the quotient on dividing x3− 2x2− x + 2 by x − 1.

         By long division method

         

                           

   

Now,

Dividend = Divisor × Quotient + remainder  

x3− 2x2− x + 2 = (x – 1) ( X2– x – 2) + 0

                       = (x – 1) (x2–2x+x–2)

                        = (x – 1) [x (x–2) + 1(x–2)]

                        = (x – 1) (x + 1) (x – 2)

(ii)   Let p(x) = x3 – 3x2−9x – 5 all the factor are there. These are ± 1, ± 2.

        By trial method, p (–1) = (–1)3– 3(1)2− 9(1) – 5

              = –1– 3–9–5     =0

        Therefore (x+1) is the factor of polynomial p(x).

       .   Let us find the quotient on dividing x3– 3x2−9x – 5 by x+1.

            By long division method

                                    

Now,

Dividend = Divisor × Quotient + remainder  

x3– 3x2−9x – 5 = (x +1) ( X2–4x – 5) + 0

                       =(x + 1) (x2–5x+x–5)

                        =(x + 1) [x (x–5) +1(x–5)]

                        =(x + 1) (x + 1) (x – 5) 

(iii)  Let p(x) = x3+ 13x2+ 32x + 20    all the factor are there.

These are ± 1, ± 2, ± 3, ± 4.

       By trial method, p (–1) = (–1)3+13(–1)2+ 32(–1) +20

                                           = –1+13–32+20   = 0    

       Therefore (x+1) is the factor of polynomial p(x).

        Let us find the quotient on dividing x3+ 13x2+ 32x + 20 by x+1

       By long division method

                                       

Now,

Dividend = Divisor × Quotient + remainder  

x3 +13x+ 32x + 20 = (x +1) ( x2 + 12x + 20) + 0

                                 =(x + 1) (x2+10x+2x+20)

                                 =(x + 1) [x (x+10) +2(x+10)]

                                 =(x + 1) (x + 2) (x + 10) 

(iv) Let p(y) = 2y3+ y2− 2y – 1 all the factor are there. These are ± 1, ± 2.

       By trial method, p (1) =2(1)3 + (1)2 – 2(1) – 1

                                        =2 + 1 – 2 – 1    =0

     Therefore (y–1) is the factor of polynomial p(y).

    Let us find the quotient on dividing 2y3+ y2− 2y – 1 by y–1.

    By long division method

                             

Now,

Dividend = Divisor × Quotient + remainder

  2y3+ y2− 2y −1 =(y − 1) (2y2+3y + 1)

                           = (y − 1) (2y2+2y

                          = (y − 1) [2y (y+1) + 1 (y + 1)]

                          = (y − 1) (y + 1) (2y + 1) 

 

Select Your CBSE Classes

Important Study materials for classes 06, 07, 08,09,10, 11 and 12. Like CBSE Notes, Notes for Science, Notes for maths, Notes for Social Science, Notes for Accountancy, Notes for Economics, Notes for political Science, Noes for History, Notes For Bussiness Study, Physical Educations, Sample Papers, Test Papers, Mock Test Papers, Support Materials and Books.